DYSLIPIDEMIA INCREASES THE RISKS FOR CEREBRO VASCULAR ACCIDENT: A CASE-CONTROL STUDY IN PANTI NIRMALA HOSPITAL, MALANG - Rea Ariyanti; Cecilia Widijati Imam (Universitas Muhammadiyah Kalimantan Timur, 2020)
Cerebro Vascular Accident (CVA) is one of the major causes of morbidity and mortality in the worldwide. Globally in 2013, stroke was the highest cause of death after heart disease and was the number three cause of long-term disability. Indonesia ranks fourth in the world after India, China and the United States and has the highest proportion of stroke sufferers in Asia.This study aims to determine the relationship of dyslipidemia and cerebro vascular accident in the Panti Nirmala Hospital. Research design is case controll study. The sample amounted to 84 respondents, consisting of 42 case groups and 42 control groups. Data analysis using logistic regression analysis. The finding shows, in patients with CVA, the percentage of respondents with dyslipidemia is 59,5%, while non-CHD is 21,4%. After controlled by a family history of CVA, Smokers, Hypertension or a history of Hypertension, and Hyperirucemia, respondents with dyslipidemia were 5.9 times more likely to have CVA than non-dyslipidemic respondents.It is recommended to the public to carry out regular medical checkup, and changing lifestyles by consuming healthy foods to control lipid profiles.